Kebun Raya Banua medicinal plant species of the Fabaceae family as popular scientific books: Practicality test - Rema Yulianti; Muhammad Zaini; Danang Biyatmoko (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
Education in the 21st century is required to produce generations who have and master various kinds of skills, one of which is critical thinking skills. Therefore, learning is needed that can prepare students to think critically. One of them is applying local potential-based learning resources developed in popular scientific book teaching materials. This study aims to examine the practicality of the content, the practicality of expectations, and the actual practicality of the popular scientific books developed. The method used is based on Tessmer's formative evaluation design. The results of the research on the readability test obtained results of 87.18% with very good criteria, based on student responses, the results were 89.60% on the practicality of expectations and 92.59% on the actual practicality with very practical criteria, and based on the implementation of popular scientific books that developed which got the results of 92.59% on the implementation of expectations and 96.69% on the actual implementation with a very good category. This result shows that a popular scientific book titled "Types of Plants in the Fabaceae Family with Medicinal Properties in the Banua Botanical Gardens" is very practical to use as enrichment material in the Higher Plant Botany (BTT) course and can improve students' critical thinking skills.Abstrak Pendidikan abad ke-21 dituntut untuk dapat menghasilkan generasi-generasi yang memiliki dan menguasai berbagai macam keterampilan salah satunya adalakah keterampilan berpikir kritis. Oleh karena itu diperlukan pembelajaran yang dapat menyiapkan peserta didik untuk berpikir kritis. Salah satunya dengan menerapkan sumber belajar berbasis potensi lokal yang dikembangkan dalam bahan ajar buku ilmiah populer. Penelitian ini bertujuan untuk menguji kepraktisan isi, kepraktisan harapan dan kepraktisan actual dari buku ilmiah populer yang dikembangkan. Metode yang digunakan adalah mengacu pada desain evaluasi formatif dari Tessmer. Hasil penelitian pada uji keterbacaan mendapatkan hasil sebesar 87,18% dengan kriteria sangat baik, berdasarkan respon mahasiswa mendapatkan hasil sebesar 89,60% pada kepraktisan harapan dan 92,59% pada kepraktisan aktual dengan kriteria sangat praktis, dan berdasarkan keterlaksanaan buku ilmiah populer yang dikembangkan yang mendapatkan hasil 92,59% pada keterlaksanaan harapan dan 96,69% pada keterlaksanaan aktual dengan kategori sangat baik. Hal ini menunjukkan bahwa buku ilmiah populer dengan judul “Jenis-Jenis Tumbuhan Famili Fabaceae Berkhasiat Obat di Kebun Raya Banua” sangat praktis digunakan sebagai materi pegayaan pada mata kuliah Botani Tumbuhan Tinggi (BTT) serta dapat meningkatkan kemampuan berpikir kritis mahasiswa.